2020
DOI: 10.1001/jamainternmed.2020.2131
|View full text |Cite
|
Sign up to set email alerts
|

The Disproportionate Burden of COVID-19 for Immigrants in the Bronx, New York

Abstract: As general internists who work in the hospitals and outpatient clinics of a large safety-net health system in the Bronx, we care for an ever-increasing number of patients with symptoms of coronavirus disease 2019 (COVID-19) who call our clinics to ask for guidance, seek care in our hospitals, and die in our wards. We are distressed by the disproportionate burden of the COVID-19 pandemic for immigrant patients.The Bronx, a borough of New York City, is one of the most ethnically diverse urban areas in the US and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
76
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 5 publications
7
76
0
Order By: Relevance
“…21,22 Recent reports have suggested a disproportionate impact of COVID-19 pandemic by social determinants of health, including characteristics such as immigration status and history, household size, and composition; therefore, future studies should consider inclusion of these variables. 23,24…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Recent reports have suggested a disproportionate impact of COVID-19 pandemic by social determinants of health, including characteristics such as immigration status and history, household size, and composition; therefore, future studies should consider inclusion of these variables. 23,24…”
Section: Discussionmentioning
confidence: 99%
“…Many experts in the field of health disparities have authored viewpoints suggesting factors which may contribute to risk of infection with or adverse outcomes from SARS-CoV-2, including language barriers, lower health literacy, higher population density, household overcrowding, reliance on public transit, overrepresentation among essential workers, lack of paid sick leave, inability to work from home, and limited physical and financial access to healthcare. 18,[21][22][23][24][25][26] However, despite widespread interest in this topic, [3][4][5][6] relatively few studies have reported data examining robust socioeconomic concepts in relationship to SARS-CoV-2 outcomes. Many COVID-19 surveillance studies on this topic do not present individual data, but aggregated outcomes over large and diverse geographic areas (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Patients preferring to undergo surgery soon after health systems reopen may be at a higher risk of postoperative morbidity and mortality. Alternatively, unaddressed concerns leading to delayed presentations may further accentuate health care disparities in disadvantaged and vulnerable populations [ [12] , [13] , [14] , [15] ].…”
mentioning
confidence: 99%